The Correlation between the Use of WhatsApp in Learning Arabic and Student's Motivation and Achievement During the Covid-19 Pandemic / العلاقة بين استخدام واتسـاب في تعليم اللغة العربية في دافعية الطلاب وإنجازهم في جائحة كوفيد-19 - Latifah, Nuri Nurul (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2021)
This study aims to determine the correlation of the use of WhatsApp as social media in learning Arabic to students' motivation and achievement during the Covid-19 Pandemic at Al-Mu'min Paseh Integrated High School Kab. Bandung for the academic year 2020/2021. The method used in this research is the descriptive correlational method, with a research sample of 30 respondents from class X and XI at "Al-Mu`min" Paseh Integrated High School Academic Year 2020/2021. Data collection technique about the use of WhatsApp as social media in learning Arabic and learning motivation by using a questionnaire and distributed with google formulir, while learning achievement is taken from the documentation of Arabic lessons in the first semester Academic Year 2020/2021, then processed using IBM SPSS Statistics 22. Based on the product-moment statistical analysis, it can be obtained that 0.872 is in the range of 0.80-1,000. So from these data, it shows that there is a positive correlation between variables X and Y1 which includes a very strong correlation between the use of WhatsApp in learning Arabic and motivation to learn Arabic. Meanwhile, it can be obtained 0.019 whose magnitude ranges from 0.00-0.199. So these data show that there is a positive correlation between variables X and Y2 which includes a very weak correlation between the use of WhatsApp in learning Arabic and learning achievement in Arabic. So the correlation of the use of WhatsApp as social media in learning Arabic during the pandemic can increase learning motivation is very strong. But for learning achievement is still very weak.